Organ-saving operation in utero-placental apoplexy. - Meerim Omurbekova (National Scientific Medical Center, 2018)
Objective: The article presents the clinical case of utero-placental apoplexy in a patient of 23 years old, who underwent innovative way of bilateral ligation of the uterine vessels according to the algorithm developed by us. Observing this algorithm, it is possible to perform an organ-preserving operation in the Couvelaire uterus.